A single CT-guided percutaneous intraosseous injection of thermosensitive simvastatin/poloxamer 407 hydrogel enhances vertebral bone formation in ovariectomized minipigs. Issue 2 (February 2016) - Tan, J.; Fu, X.; Sun, C.; Liu, C.; Zhang, X.; Cui, Y.; Guo, Q.; Ma, T.; Wang, H.; Du, G.; Yin, X.; Liu, Z.; et al.
Abstract Summary The ultimate goal of osteoporosis treatment is prevention of fragile fracture. Local treatment targeting specific bone may decrease the incidence of osteoporotic fractures. We developed an injectable, thermosensitive simvastatin/poloxamer 407 hydrogel; a single CT-guided percutaneous intraosseous injection augmented vertebrae in ovariectomized minipigs. Introduction The greatest hazard associated with osteoporosis is local fragility fractures. An adjunct, local treatment might be helpful to decrease the incidence of osteoporotic fracture. Studies have found that simvastatin stimulates bone formation, but the skeletal bioavailability of orally administered is low. Directly delivering simvastatin to the specific bone that is prone to fractures may reinforce the target bone and reduce the incidence of fragility fractures. Methods We developed an injectable, thermosensitive simvastatin/poloxamer 407 hydrogel, conducted scanning electron microscopy, rheological, and drug release analyses to evaluate the delivery system; injected it into the lumbar vertebrae of ovariectomized minipigs via minimally invasive CT-guided percutaneous vertebral injection. Three months later, BMD, microstructures, mineral apposition rates, and strength were determined by DXA, micro-CT, histology, and biomechanical test; expression of VEGF, BMP2, and osteocalcin were analyzed by immunohistochemistry and Western blots. Results Poloxamer 407 is an effective controlled delivery system for intraosseous-injected simvastatin. A single injection of the simvastatin/poloxamer 407 hydrogel significantly increased BMD, bone microstructure, and strength; the bone volume fraction and trabecular thickness increased nearly 150 %, bone strength almost doubled compared with controls (allP  < 0.01); and induced higher expression of VEGF, BMP2, and osteocalcin. Conclusions CT-guided percutaneous vertebral injection of a single simvastatin/poloxamer 407 thermosensitive hydrogel promotes bone formation in ovariectomized minipigs. The underlying mechanism appears to involve the higher expression of VEGF and BMP-2.